The Effectiveness of Crime Prevention with Corporal Punishment in Nanggroe Aceh Darussalam - Ahmad Nurozi; Dadan Muttaqien (Millah: Journal of Religious Studies, 2021)
The enactment of corporal punishment in Nanggroe Aceh Darussalam is one of the efforts of local government in realizing Islamic society. This corporal punishment is one of the alternatives for national criminal law policy in preventing crime which keeps increasing. This research aims to identify the background, implementation, and effectiveness of the corporal punishment in Qanun No. 14 Year 2003 for crime prevention and establishment of Islamic society in Nanggroe Aceh Darussalam Province. This research is the field research, in Banda Aceh City, with the normative and empirical juridical approaches. Primary, secondary, and tertiary data sources were obtained through the field and document studies related to the topic of research using the content of qualitative descriptive analysis in which the instrument of research is the researcher. This research shows the result that implementation of the corporal punishment in Nanggroe Aceh Darussalam is still limited to the caning as one of the criminal sanctions, particularly in handling the case of khalwat (close proximity). However, the implementation of corporal punishment, in this case, has a quite effective role in the process of establishing an Islamic society in Nanggroe Aceh Darussalam.Efektifitas Penanggulangan Kejahatan Dengan Pidana Badan Di Nangroe Aceh DarusssalamPemberlakuan pidana badan di Nangroe Aceh Darusssalam merupakan salah satu bentuk upaya pemerintah setempat dalam mewujudkan masyarakat Islami. Pidana badan ini juga merupakan alternatif kebijakan hukum pidana nasional dalam penanggulangan kejahatan yang semakin meningkat. Tujuan penelitian adalah untuk mengetahui latarbelakang, pelaksanaan dan efektifitas hukuman pidana badan dalam Qanun Nomor 14 Tahun 2003 bagi penanggulangan kejahatan dan pembentukan masyarakat Islami di Propinsi Nanggroe Aceh Darussalam. Penelitian ini merupakan penelitian lapangan, yaitu di kota Banda Aceh dengan pendekatan yuridis normative dan yuridis empiris. Adapun sumber data primer, sekunder dan tertier diperoleh melalui studi lapangan dan studi dokumen terkait topik penelitian dengan menggunakan konten analisis deskriptif kualitatif dengan instrumen penelitian adalah peneliti itu sendiri. Hasil penelitian menunjukan penerapan pidana badan di Nanggroe Aceh Darussalam sampai saat ini masih terbatas pada penggunaan pidana cambuk sebagai salah satu jenis sanksi pidana, khususnya dalam penanganan perkara khalwat (mesum). Meskipun demikian, penerapan pidana badan dalam perkara tersebut memiliki peran yang cukup efektif dalam proses pembentukan masyarakat Islami di wilayah Nangroe Aceh Darusssalam.